THE EFFECT OF ACCOUNT RECEIVABLE TURNOVER AND CASH TURNOVER ON LIQUIDITY AT PT PLN PERSERO - Anisya Lestari; Febriyani Eka Supriatin; Agustina Eka Harjanti (Vocational School, Universitas Sebelas Maret (UNS), Indonesia, 2022)
This study aimed to partially examine the effect of account receivable turnover and cash turnover on liquidity at PT PLN Persero, simultaneously evaluate the effect of account receivable turnover and cash turnover on liquidity at PT PLN Persero, and identify the financial ratios (the influence of account receivable turnover and cash turnover), which are more dominant in influencing account receivable turnover and cash turnover on liquidity (current ratio) at PT PLN Persero. Samples were taken from the financial statements of PT PLN Persero from 2010 to 2019 using the purposive sampling technique. The classical assumption tests (normality test, multicollinearity test, heteroscedasticity test, and autocorrelation test) were applied in this study. Multiple linear regression was utilized for analysis. To examine hypotheses, t-test, F-test, and coefficient of determination test were used. The results of statistical data tests show that partially account receivable turnover has no significant effect on liquidity (current ratio) and cash turnover has no significant effect on liquidity (current ratio). Thus, users of financial statements can consider these ratios as reference considerations in making decisions.